Investigation of the Relationship between the Ecological Identity of Teacher Candidates and Environmental Risk Perceptions Relationship Between the Ecological Identity and Environmental Risk Perceptions - Derya Sönmez; Gamze Hastürk (Science Education International, 2023)
In this research, it was aimed to determine the relationship between the ecological identities of primary school teacher candidates and their environmental risk perceptions. The research was conducted with teacher candidates from a Turkish university located in the Central Black Sea Region in the fall semester of the 2021–2022 academic year. The research used the “Ecological Identity Scale” and the “Scale of Environmental Risk Perception.” Both descriptive and inferential statistical analyses were used in the data obtained in the study. According to the research findings, the ecological identities of primary school teacher candidates and the sub-dimensions of identity and centrality were at the medium level; the differentiation sub-dimension was found to be at a high level. Similarly, it has been determined that there was a moderately positive and statistically significant relationship between the ecological identities of the primary school teacher candidates and their environmental risk perceptions. It has been determined that there was no statistically significant difference in the ecological identities of the primary school teacher candidates according to gender, grade level, or environmental education course. It was found that there was no statistically significant difference in the environmental risk perceptions of the primary school teacher candidates according to gender, grade level, or environmental education course. In line with the results obtained as a result of the research, educational activities can be carried out to improve the ecological identities and environmental risk perceptions of primary school teacher candidates. This research is important in terms of determining the relationship between ecological identity and environmental risk perception of prospective primary school teachers, who will be effective in the formation of ecological identity and environmental risk perception that individuals can gain at a young age. In line with this importance and the results of the research, suggestions that will increase the levels of ecological identity and environmental risk perception of prospective primary school teachers are given.